'A History of Islamic Societies' oleh Ira M Lapidus: Kritikan terhadap Prakata Karyanya : 'A History of Islamic Societies' by Ira M Lapidus: A Critical study on Its Preface - Ali @ Mat Zin, Aizan; Ibrahim, Muhammad Syahmi (Journal of Al-Tamaddun, 2021)
This study aims to analyse issues in the preface section of a literature written by an orientalist Ira M Lapidus. Students of social science and humanities at university level refer to the book in their study on Islamic societies. Data collection in this study gathered by using method of documentation. Then all the collected data were analysed by using content analysis in addition to inductive, deductive and comparative methods. Finding shows that there is issue of differences in data interpretation done by Ira M. Lapidus. This is due to his reference are mainly secondary rather than primary sources. In conclusion, this article strongly suggest the importance of primary source in writing Islamic history.